Development of butter cookies using seaweed (kappaphycus alvarezii) flour and overripe banana sweetener by response surface methodology and sensory evaluation - Linlin, Nie (2024)
This study was conducted to develop a high dietary fibre and low glycaemic index healthy cookie for using seaweed flour (Kappaphycus alvarezii) to replace wheat flour, overripe banana sweetener (OBS) replacing table sugar, and butter replacing margarine. A total of three factors were set, each with a different percentage of seaweed flour (0%, 4%, 4%), OBS (0%, 50%,100%), and butter (50%, 50%, 100%) to replace flour, sugar and margarine. The ratios/levels of seaweed flour, OBS, and butter in the butter cookies’ formulation were optimized using Box Behnken design of response surface methodology (RSM). The physicochemical properties of cookies, such as texture profile analysis, nutrient analysis, total dietary fibre, and colour, were also assessed. Sensory evaluations involving 30 untrained panellists were conducted to determine the acceptability levels of the cookie. The results showed that the increment of seaweed flour in the formulations increased the weight (18.22 g), crispness (2.21 mm), and thickness (10 mm). Furthermore, the addition of seaweed flour reduced the diameter (53.8 mm), firmness (2.05 kg), and spread ratio (5.38). Two optimal formulations were obtained: experiment 12 (seaweed 4%, OBS 100%, butter 50%) and experiment 14 (seaweed 4%, OBS 50%, butter 50%). These two experiments were subjected to organoleptic evaluations and nutritional analyses in comparison with the control (seaweed 0%, OBS 0%, butter 50%). The addition of 4% seaweed flour, 50% OBS, and 50% butter to the formulation increased the composition of ash (2.53%), moisture (8.02%), and fat (20.92%), while the composition of protein (6.88%) and carbohydrate (62%) was slightly reduced. In addition, there was an increase in total dietary fibre (16.61%) for 4% seaweed-contained cookies as compared to the control sample. In the sensory evaluation, the overall scores for the control cookie (0%) and the 4% cookie combined with seaweed flour were not significantly different for all attributes. However, the addition of 4% seaweed flour and 50% OBS resulted in the highest scores for aroma, flavour, and overall acceptance attributes. In conclusion, substituting 4% seaweed flour to replace wheat flour, 50% OBS to replace table sugar, and 50% butter to replace margarine could be an effective combination to produce nutritious and tasty cookies. Therefore, Kappaphycus alvarezii able to improve the nutritional composition of cookie and has the potential to be used as an alternative ingredient for the development of high dietary fibre and nutritious bakery products.